Systematic Review Hubungan Antara Status Gizi Dan Siklus Menstruasi Dengan Kejadian Anemia Pada Remaja Putri - Wahyuni, Sri; Syamiyah, Najah (JOURNAL OF BAJA HEALTH SCIENCE, 2024)
Globally according to the Word Health Organization (WHO) in the worldwide prevalence of anemia in 2015 shows that the prevalence of anemia in women is 42.6%. the prevalence of anemia in women in Southeast Asia is 41.9%. The method used in this study used literature studies from several international and national journals. This method is used to summarize a topic so as to increase understanding. The literature study presents previously published material and the literature review provides a summary of the best and relevant publications. The results of research that has been conducted by Santi on patients who came for treatment to the UIN Sunan Ampel clinic from 2015-2917 showed that there were as many as 192 female patients experiencing menstrual disorders. These menstrual disorders are menstrual cycle / pattern disorders, menstrual duration, and other disorders (Santi &; Pribadi, 2018). That there is a relationship between nutritional status and menstrual cycles with the incidence of anemia in adolescent girls.